Erratum: Searches for continuous gravitational waves from nine young supernova remnants (ApJ (2015) 813 (39) DOI: 10.1088/0004-637X/813/1/39) - Aasi, J.; Abbott, B. P.; Abbott, R.; Abbott, T.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V.; et al. (American Astronomical Society, 2021)
Equation (7) of the published article (Aasi et al. 2015) is in error; it should read (Equation presented). The upper limits on ò presented in the published article are unaffected by this error. Equation (8) of the published article is in error; it should read (Equation presented) The upper limits on α presented in Figure 3 and Table 4 of the published article were computed incorrectly. The revised Figure 3 (bottom) shows the corrected upper limits on α for the G266.2-1.2 (Vela Jr.) wide search. The revised Table 4 is provided here. The correct lowest upper limit on α (quoted in the Abstract of the published article) is 3 × 10-6. Figure 4 shows the incorrect and corrected upper limits on α for the G266.2-1.2 (Vela Jr.) wide search, which have been surpassed by upper limits from Abbott et al. (2019).